Antioxidant and Anti-Inflammatory Activities of Phytochemicals from Ruellia tuberosa - Trinh Nhat Thi Pham; Tuan Trong Nguyen; Thuy Le Thi Nguyen; An Minh Nguyen Tran; Tuan Ngoc Nguyen; Danh Thanh Tong; Dung Tien Le (Journal of Chemistry)
In Vietnam, the aerial parts of Ruellia tuberosa L. are used to treat stress oxidation and inflammatory symptoms in diabetes mellitus. The present study was designed to determine the antioxidant and inflammatory inhibition activities of Ruellia tuberosa L. extract (RTE) and those of the isolated compounds by column chromatography. The crude ethanol extract and ethyl acetate fraction exhibited potent antioxidant activity in the 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) and 2,2-azinobis-(3-ethylbenzothiazoline-6-sulfonate) (ABTS) assays with an IC50 of 25.18 and 14.71 (DPPH test) and 18.22 and 15.27 µg/ml (ABTS test), respectively. The RTE contained high concentrations of polyphenols (308.21 mg GAE/g) and moderate concentrations of flavonoids (97.80 mg QE/g). In the anti-inflammatory screening assay, the crude ethanol extract, ethyl acetate, and methanol fractions suppressed the release of IL-6 and nitric oxide production, but the production of IL-10 was not enhanced in LPS-induced RAW 264.7 cells. Three potential anti-inflammatory compounds as hispidulin (6), physalin E (7), and physalin D (8) along with five other compounds named myricitrin (1), afzelin (2), apigenin (3), taraxerol (4), and lupeol (5) were isolated and identified from the ethyl acetate fraction. Physalin D (8) exhibited a strong, dose-dependent anti-inflammatory activity by inhibiting the production of IL-6 proinflammatory cytokines; however, the IL-10 expression was independent of its concentration in macrophages at noncytotoxic concentrations ranging from 5 to 40 μg/mL. Based on the data obtained, compounds 6–8 sourced from Ruellia tuberosa L are potentially bioactive compounds for the treatment of inflammation symptoms in type 2 diabetes mellitus.